Interaction between coronaviruses and the autophagic response - Yu, Jiarong; Ge, Shengqiang; Li, Jinming; Zhang, Yongqiang; Xu, Jiao; Wang, Yingli; Liu, Shan; Yu, Xiaojing; Wang, Zhiliang (Frontiers in Cellular and Infection Microbiology, 2024)
In recent years, the emergence and widespread dissemination of the coronavirus SARS-CoV-2 has posed a significant threat to global public health and social development. In order to safely and effectively prevent and control the spread of coronavirus diseases, a profound understanding of virus-host interactions is paramount. Cellular autophagy, a process that safeguards cells by maintaining cellular homeostasis under diverse stress conditions. Xenophagy, specifically, can selectively degrade intracellular pathogens, such as bacteria, fungi, viruses, and parasites, thus establishing a robust defense mechanism against such intruders. Coronaviruses have the ability to induce autophagy, and they manipulate this pathway to ensure their efficient replication. While progress has been made in elucidating the intricate relationship between coronaviruses and autophagy, a comprehensive summary of how autophagy either benefits or hinders viral replication remains elusive. In this review, we delve into the mechanisms that govern how different coronaviruses regulate autophagy. We also provide an in-depth analysis of virus-host interactions, particularly focusing on the latest data pertaining to SARS-CoV-2. Our aim is to lay a theoretical foundation for the development of novel coronavirus vaccines and the screening of potential drug targets.